ANALISIS KUALITAS PELAYANAN JASATERHADAP KEPUASAN NASABAH PADA BANK BNIDI WILAYAH JAKARTA SELATAN - Nursila Nisa Dewi (2013)
Effect of service quality on customer satisfaction with the Bank in South Jakarta. In this study sample was 100 respondents taken BNI teen or adult clients who are customers in South Jakarta. This study uses non-random sampling method because of the large population is not known for certain or any element of the population does not have the same probability to be sampled. Sampling method used was purposive sampling method. This study uses techniques Performance Analysis Important or Importance and performance analysis of customer satisfaction. Important Performance Analysis test is performed to measure the ratio between the level of customer satisfaction with the level of interest (customer expectations ). The results showed that the majority of respondents said they were satisfied with the service of Bank BNI 46 South Jakarta. Most of the tested factors are in quadrant B is maintained so that the performance can be concluded that the high expectations of the majority of the respondents have been met. The results showed that there is a significant relationship between service quality on customer satisfaction this can be seen in quadrant B (keep achievement) showed the fulfillment of consumer expectations can create customer satisfaction.